Musculoskeletal melioidosis in a 33-year-old farmer presenting with the right leg cellulitis: A case report from North India - Jindal, Anmol; Chawla, Kunal; Gulati, Shipra; Dessai, Rishikesh (Indian Journal of Case Reports, 2024)
Melioidosis, caused by Burkholderia pseudomallei, has been described as “the great mimicker” due to its varied clinical presentation. Musculoskeletal melioidosis is a rare presentation of this disease, and here we report a 33-year-old male, farmer from Madhya Pradesh, who presented with fever for 2 months and right leg swelling for 25 days. He was treated elsewhere as cellulitis and managed with intravenous antibiotics and fasciotomy. Magnetic resonance imaging knee and leg showed diffuse osteomyelitis of the upper tibia with similar tiny foci and sinus tract present. A diagnosis of the right knee septic arthritis with multifocal osteomyelitis was made. Focal pus culture grew pansensitive B. pseudomallei. He was started on Inj. Meropenem and oral cotrimoxazole tablet. He also underwent right tibial debridement, sequestrectomy, and saucerisation. He was discharged after initial therapy and has improved significantly on follow-up. This case highlights a very common clinical condition caused by a rather uncommon etiological agent and therefore renumerates the importance of insightful clinical suspicion with appropriate use of investigations and treatment options to prevent further morbidity and mortality.